PENDAMPINGAN ORIENTASI PRIBUMISASI ISLAM MELALUI MODERASI BERAGAMA DI MASJID USWATUN HASANAH SUKAHATI CIBINONG KABUPATEN BOGOR - M. Adlan Nawawi; Lazimatun Nazhifah; Kholilurrohman Kholilurrohman; Abd Aziz; EE Junaedi Sastradiharja; Zuhrupatul Jannah (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2025)
Religious moderation is the understanding and practice of worship in religion, balanced, not extreme, and excessive. The phenomenon of fanaticism and blind taqlid in society gives birth to attitudes that tend to be anarchist and exclusivism between various groups. Abdur Rahman Wahid or who is familiarly called Gus Dur invites us to reinterpret religion as a way of unifying in the framework of community life. This paper aims to explain how to carry out a religious life among the many religions and beliefs in the community, in order to revive a harmonious and respectful society